The Elephant and the Blind Men: Making Sense of PARP Inhibitors in Homologous Recombination Deficient Tumor Cells - De Lorenzo, Silvana; Patel, Anand; Hurley, Rachel; Kaufmann, Scott H. (Frontiers in Oncology, 2013)
Poly(ADP-ribose) polymerase 1 (PARP1) is an important component of the base excision repair (BER) pathway as well as a regulator of homologous recombination (HR) and nonhomologous end-joining (NHEJ). Previous studies have demonstrated that treatment of HR-deficient cells with PARP inhibitors results in stalled and collapsed replication forks. Consequently, HR-deficient cells are extremely sensitive to PARP inhibitors. Several explanations have been advanced to explain this so-called synthetic lethality between HR deficiency and PARP inhibition: i) inhibition of base excision repair leading to enhanced DNA double-strand breaks, which cannot be repaired in the absence of HR; ii) trapping of inhibited PARP1 at sites of DNA damage, which inhibits access of other repair proteins; iii) failure to synthesize poly(ADP-ribose) polymer, which is required to recruit mutant BRCA1 to sites of DNA damage; and iv) activation of the NHEJ pathway, which selectively induces error-prone repair in HR-deficient cells. Here we review evidence regarding these various explanations for the ability of PARP inhibitors to selectively kill HR-deficient cancer cells.